Determination of Optimum Mixture Between FABA and Local Fill Soil for Road Embankment. Case study: Road Preservation of Sp. Kereng - Bereng Bengkel – Pilang – Pulang Pisau, Central Kalimantan - Syauqi Al Ghifari, Raden Hisyam; Mochtar, Noor Endah; Soendiarto, Soendiarto (Journal of Infrastructure & Facility Asset Management, 2024)
The road connecting Simpang Kereng, Bereng Bengkel, Pilang, and Pulang Pisau is part of the road network between two big cities in Kalimantan Island, Palangkaraya and Banjarmasin. These two big cities have a lot of activities that generate very high traffic volumes. Therefore, BPJN Central Kalimantan plans to make road improvements by widening the road. For this work, it needs a lot of good fill soil material that is very difficult to find in the nearest site; consequently, the cost of this project becomes very expensive.  This condition can be done by mixing the local fill (good quality) soil with fly ash and bottom ash (FABA) as waste of Pulang Pisau Power Plant (PLTU PP). Because of that it needs to determine the optimum mixture between FABA and the local fill soil. The local soil, fly ash, and bottom ash can be classified as A-3 or SP, A-2-5 or SM, and A-3 or SP, respectively. Three different percentages of local soil, bottom ash, and fly ash mixtures were prepared (50:50:0), (40:40:20), and (30:30:40). They were tested to see which mixture that met the criteria for road embankments according to the General Specifications of Bina Marga Revision 2, 2018. The test results show that by mixing the local soil with FABA, the soaked CBR value decreases with the increase of FABA. The soaked CBR values of the local soil and the mixing materials, 50:50:0 (without fly ash), 40:40:20, and 30:30:40 are 17,78%, 17.22%, 15,87%, and 14.46%, respectively. It means that all the mixing materials meet the criteria for road embankment materials. Therefore, selection of the optimum mixing materials is based on the lowest unit price for material installed in the field, that is 30:30:40 mixture (30% local soil, 30% bottom ash, and 40% fly ash).